METHODS OF INSTRUCTION BASED ON AUDIOVISUALS TO INCREASE STUDENTS' INTEREST IN LITERACY IN ELEMENTARY MADRASAHS - Jamaluddin; Septantiningtyas, Niken; Fajri, Zaenol (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students at the Madrasah Ibtidaiyah level continue showing a comparatively low degree of interest in literacy, particularly reading and writing. The less engaging and frequently boring teaching methodology is one of the reasons. Using audio-visual materials is one of the creative learning strategies required to solve this issue. This media can boost students' interest in literacy-related tasks by presenting educational content more engagingly and understandably. Given this context, this study aims to assess how well Madrasah Ibtidaiyah Raudlatul Hidayah's use of audio-visual-based teaching techniques increases students' interest in literacy. This study combines a descriptive method with a qualitative approach. Teachers were interviewed, students were given questionnaires to complete as the primary respondents, and observations of teaching and learning activities were used to gather data. According to the study's findings, using audio-visual materials, including instructional videos, animations, and interactive graphics, helped pupils become more interested in reading and writing. Pupils started to gather written tasks actively, became more excited about paying attention in class, and began searching for extra reading independently. Teachers also thought this approach improved class interaction, facilitated time management, and helped pupils grasp the content more quickly. Nevertheless, challenges must be addressed, including a lack of technology gadgets, erratic internet connections, and instructor proficiency with digital media. As a result, specialised training and sufficient infrastructure are required. The audio-visual approach has raised students' attention and reading levels and is a valuable teaching tool in the digital age